Influence of Football on Physiological Cardiac Indexes in Professional and Young Athletes - Francavilla, Cristian V.; Sessa, Francesco; Salerno, Monica; Albano, Giuseppe D.; Villano, Ines; Messina, Giovanni; Triolo, Fabio; Todaro, Lorenzo; Ruberto, Maria; Marsala, Gabriella; Cascio, Orazio; Mollica, Maria P.; et al. (Frontiers in Physiology, 2018)
Background: After long-term intensive training, considerable morphological and functional heart changes occur in professional athletes. Such changes arise progressively and regress upon interruption of the physical activity. Morphological and functional alterations on heart are known as “Athlete’s heart” condition. Objective: This study aims to compare echocardiographic parameters in two different groups of professional athletes. Furthermore, a prospective study is performed analyzing the echocardiographic changes occurring in 12 professional players in three years of follow-up. Materials and methods: 78 football players were examined from July 2011 to May 2016 (40 enrolled in Group A and 38 in Group B). 12 players of GROUP A were followed for 3 consecutive seasons. The general clinical examination, the cardiopulmonary evaluation, the ECG, the ergometer stress test, the spirometric examination and the standard cardiac eco color doppler test were recorded. Results: Left ventricle dimensions, left atrium dimensions, and interventricular septum dimensions were higher in A players than in B players. Moreover, following up 12 players for three years, a statistically significant increase of such values was observed. Discussion: In A players, higher dimensions of the left chambers and the interventricular septum were observed, compared to B players. No statistically significant difference was found regarding the ejection fraction. The three years follow-up showed a statistically significant increase of both left chambers and interventricular septum dimensions, particularly in the second and third year. Conclusions: These findings demonstrated that A players have higher echocardiographic parameters respect to B players. The results of this study support the scientific theory that long-term intensive training influences heart function, inducing “athlete’s heart” with morphological adaptations. No significant echocardiographic variation within the examined sample was observed for different roles (goalkeeper, defender, midfielder, or attacker) or skills of individual players.